Measles susceptibility in maternal-infant dyads—Bamako, Mali. Issue 9 (23rd February 2022) - Dixon, Meredith G.; Tapia, Milagritos D.; Wannemuehler, Kathleen; Luce, Richard; Papania, Mark; Sow, Samba; Levine, Myron M.; Pasetti, Marcela F.
Highlights: Maternal antibodies correlated with infant seroprotective status at birth. Ten percent of Malian newborns were susceptible to measles at birth. Nearly all infants were measles susceptible by six months of age. Improved strategies are needed to protect susceptible infants from measles death. Abstract: Measles is endemic in Africa; measles mortality is highest among infants. Infant measles antibody titer at birth is related to maternal immune status. Older mothers are likelier to have had measles infection, which provides higher antibody titers than vaccine-induced immunity. We investigated the relationship between maternal age and measles susceptibility in mother-infant pairs in Mali through six months of infancy. We measured serum measles antibodies in 340 mother-infant pairs by plaque reduction neutralization test (PRNT) and calculated the proportion of mothers with protective titers (>120 mIU/mL) at delivery and the proportion of infants with protective titers at birth, and at three and six months of age. We explored associations between maternal age and measles antibodies in mothers and infants at the timepoints noted. Ten percent of Malian newborns were susceptible to measles; by six months nearly all were. Maternal and infant antibody titers were highly correlated. At delivery, 11% of mothers and 10% of newborns were susceptible to measles. By three and six months, infant susceptibility increased to 72% and 98%, respectively. Infants born to younger mothers were most susceptible at birth and three months. Time to susceptibility was 6.6 weeks in infants born to mothers with measles titer >120–<430 mIU/mL versus 15.4 weeks when mothers had titers ≥430 mIU/mL. Maternal and newborn seroprotective status were positively correlated. Improved strategies are needed to protect susceptible infants from measles infection and death. Increasing measles immunization coverage in vaccine eligible populations, including nonimmune reproductive-aged women and older children should be considered.